Lysophosphatidylcholine Induces NLRP3 Inflammasome-Mediated Foam Cell Formation and Pyroptosis in Human Monocytes and Endothelial Cells - Corrêa, Rafael; Silva, Luís Felipe Fonseca; Ribeiro, Dalila Juliana Silva; Almeida, Raquel das Neves; Santos, Igor de Oliveira; Corrêa, Luís Henrique; de Sant'Ana, Lívia Pimentel; Assunção, Leonardo Santos; Bozza, Patrícia T.; Magalhães, Kelly Grace (Frontiers in Immunology, 2020)
Foam cells are specialized lipid-loaded macrophages derived from monocytes and are a key pathological feature of atherosclerotic lesions. Lysophosphatidylcholine (LPC) is a major lipid component of the plasma membrane with a broad spectrum of proinflammatory activities and plays a key role in atherosclerosis. However, the role of LPC in lipid droplet (LD) biogenesis and the modulation of inflammasome activation is still poorly understood. In the present study, we investigated whether LPC can induce foam cell formation through an analysis of LD biogenesis and determined whether the cell signaling involved in this process is mediated by the inflammasome activation pathway in human endothelial cells and monocytes. Our results showed that LPC induced foam cell formation in both types of cells by increasing LD biogenesis via a NLRP3 inflammasome-dependent pathway. Furthermore, LPC induced pyroptosis in both cells and the activation of the inflammasome with IL-1β secretion, which was dependent on potassium efflux and lysosomal damage in human monocytes. The present study described the IL-1β secretion and foam cell formation triggered by LPC via an inflammasome-mediated pathway in human monocytes and endothelial cells. Our results will help improve our understanding of the relationships among LPC, LD biogenesis and NLRP3 inflammasome activation in the pathogenesis of atherosclerosis.